FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN DAN KESEJAHTERAAN PENGRAJIN INDUSTRI KERAJINAN ANYAMAN BAMBU DI KECAMATAN SUSUT - suryandari, kadek kharisma; Darsana, Ida Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No.4, April 2018 (pp. 617-867), 2018)
Bangli is one of the districts in Bali that relies on industrial growth by optimizing the abundant natural resources to increase the income of its people. This research wanted to know partially and simultaneously influence of variable of capital, labor variable and work experience variable to income variable and welfare varieties of craftsmen in woven bamboo handicraft industry in Susut Subdistrict, Bangli regency. The number of samples taken as many as 90 craftsmen with proportionale stratified random sampling method. The results of analysis using multiple linear regression analysis states that simultaneously and partially variable of capital, labor variable, and work experience variable give positive and significant influence to earnings and welfare of artisans in woven bamboo handicraft industry in Kecamatan Susut. Suggestions for Bangli Regency Government to give more convenience in accessing capital to craftsmen and often monitoring and socialization such as special training to add skill craftsmen so as to create new innovation for its products. Keywords: capital, labor, work experience, income, welfare